Single bond activated AIE of platinum(II) complex achieving expeditious oxygen monitoring and high-efficiency felodipine identification. (September 2022) - Di, Ling; Wang, Ziang; Yu, Zongbao; Cao, Qingsong; Wang, Hao; Xing, Yang; Yang, Zhanxu; Xia, Zhengqiang
Abstract: Planar substituents such as carbazole possess excellent electronic characteristics and photoelectric properties. However, the undesirable aggregation-caused quenching (ACQ) phenomenon of luminogens is commonly triggered in solid and aggregation states by the modification of planar substituents, resulting in declined photophysical properties and degenerative device performances. Herein, an extraordinary aggregation-induced emission (AIE) phenomenon of the platinum(II) complex PtPhenCz containing a planar carbazole group is found accidently. The variation tendency of dipole moments and the planarity analysis of molecular fragments verify that the highly active rotation of the carbazole group caused by a single chemical bond activates the AIE of PtPhenCz. By the combination of AIE character and room-temperature phosphorescence (RTP) nature of PtPhenCz, expeditious quenching/recovery response of 5.1 s is demonstrated by the degressive thickness of PtPhenCz/ethocel films. The AIE property of PtPhenCz efficaciously improves the oxygen sensitivity of ethocel films. Furthermore, AIE-active PtPhenCz demonstrates outstanding luminescent detection performance to antihypertensive felodipine. Spectral overlaps, noncovalent interaction analysis, and hole-electron population analysis indicate that the synergistic effect of resonance energy transfer and high-efficiency electron transfer result in the high detection efficiency. Noteworthily, selective visualization of felodipine under the interference of seven commonly used drugs is firstly achieved by PtPhenCz. Graphical abstract: Image 1 Highlights: An extraordinary AIE of platinum(II) complex containing the planar carbazole is activated by a single chemical bond. Expeditious quenching/recovery response in 5.1 s is demonstrated by a hypersensitive oxygen sensing thin film. Selective visualization of felodipine under the interference of seven common drugs is for the first time achieved.